Business Strategy Formulation for Multi Makmur Mandiri - Budiman, Harry; Hariandja, Evo S (The Indonesian Journal of Business Administration, 2013)
Multi Makmur Mandiri is a company dealing in construction material trading and located in Garut Regency, West Java Province, Indonesia. As of recent years, Multi Makmur Mandiri faced with requirement of management regeneration. In order to facilitate it Multi Makmur Mandiri changes its business entity status from sole proprietorship to limited partnership company in 2012. These two changes required the company to restructure its organization and readjust its business strategy in order to maintain and improve its competitive advantage. The process of formulating business strategy may be divided into three main phases; strategic analysis, strategic analysis output and strategy identification, selection and implementation During strategic analysis, external analysis and internal analysis in order to provide output which will be to identify opportunities, threats, strengths and weaknesses. These 4 elements would then be used to identify business strategy alternatives which would be selected based on predetermined criteria. The result of selection process would end as proposed business strategies and its implementation plan. This paper’s objective is to provide business strategies suitable with Multi Makmur Mandiri’s situation. These proposed business strategies are expected to help Multi Makmur Mandiri to maintain and improve its competitive advantage. The result of this strategy formulation is: a). Value proposition based on product line breadth; b). Organization structure building; c). Implementation of integrated information system. Keyword: strategic market management, business strategy, formulation, construction material, building material.